Representation of Cultural Identity of Women and Girls in the Cover Designs of Children's Stories in Arab Countries - Ghufran Brimo; Effatolsadat Afzaltousi (زن در فرهنگ و هنر)
Illustrating children's book covers plays a significant role in conveying cultural concepts to them. The cultural identity of children can be indirectly reinforced by images that reference specific cultural concepts of a community or a region.This study aims to answer the question of how the cultural identity of girls and women is represented in the cover illustrations of children's stories in Arabic-speaking countries. To gain insight into cultural identity, particularly Arab identity among Arabic-speaking girls and women, it analyzes the statistical population. In this context, 249 cover designs from six Arab countries including Egypt, Iraq, Lebanon, Syria, Saudi Arabia, and the UAE were examined for the age group (B). Results show that the UAE is the most wealthy nation in terms of cultural visual representations, while Syria is the least prosperous in this regard. Arab girls' and women's faces are prominent in most images, and the palm tree, a symbol of natural geography, plays a significant role in Arab identity, especially in Iraq publications. Older women on the cover illustrations are often veiled, and the veil is one of the most prominent visual symbols. Nevertheless, in Lebanon and Syria, this symbol is less prominent across all age categories. It appears that a general conclusion can be derived regarding the identity of Arab girls and women on the covers of children's books in Arabic-speaking countries in the present study. This identity is a combination of Arab and Islamic identity, with a particular emphasis on geographical and natural symbols.